High-resolution dissection of photosystem II electron transport reveals differential response to water deficit and heat stress in isolation and combination in pearl millet [Pennisetum glaucum (L.) R. Br.] - Shanker, Arun K.; Amirineni, Sushma; Bhanu, Divya; Yadav, S. K.; Jyothilakshmi, N.; Vanaja, M.; Singh, Jainender; Sarkar, B.; Maheswari, M.; Singh, V. K. (Frontiers in Plant Science, 2022)
Heat and Water Deficit Stress (WDS) tend to impede and restrict the efficiency of photosynthesis, chlorophyll fluorescence, and maximum photochemical quantum yield in plants based on their characteristic ability to interfere with the electron transport system in photosystem II. Dissection of electron transport pathway in Photosystem II (PSII) under water deficit and Heat Stress (HS) can be insightful in gaining knowledge on the various attributes of the photosynthetic performance of the plant. We attempt a high-resolution dissection of electron transport in PSII with studies on chlorophyll a fast fluorescence kinetics and Non-Photochemical Quenching (NPQ) as a response to and recovery from these stresses in pearl millet (Pennisetum glaucum (L.) R. Br.) in isolation and combination. In this study, we bring out the mechanisms by which both heat and water stress, in isolation and in combination, affect the photosynthetic electron transport in Photosystem II. Our results indicate that Oxygen Evolution Complex (OEC) damage is the primary effect of heat stress and is not seen with the same intensity in the water-stressed plants. Low exciton absorption flux in heat stress and combined stress was seen due to OEC damage, and this caused an electron transport traffic jam in the donor side of PS II. Both the specific energy flux model and the phenomenological flux model developed from the derived values in our study show that water deficit stress in combination with heat stress has a much stronger effect than the stresses in isolation on the overall electron transport pathway of the PS II in pearl millet plants.